2019
DOI: 10.5539/elt.v12n5p55
|View full text |Cite
|
Sign up to set email alerts
|

The Vocabulary Knowledge of Saudi EFL Tertiary Students

Abstract: This study examines the vocabulary knowledge of 120 Saudi tertiary students in order to scrutinise their ability to communicate in English. A vocabulary test constructed by Nation and Beglar (2007) was utilised in the study. The findings revealed that the mean vocabulary size of Saudi EFL tertiary students was roughly 3000 words. Nevertheless, most of the participants achieved low scores in the vocabulary low frequency levels. Some participants were unable to answer any item correctly in these low and mid freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Considering the interpretation of data, EFL students showed a significant improvement their performance, as evident in the post-test scores. This also shows consistency with the findings in other studies (Zhao,2009;Noor & Amir, 2009;Omar, 2015;Taheri & Davoudi, 2016;Baskin et al, 2017;Altalhab, 2019). Hence, explicit training on the usage of vocabulary acquisition procedures makes it easier for students to acquire new words.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering the interpretation of data, EFL students showed a significant improvement their performance, as evident in the post-test scores. This also shows consistency with the findings in other studies (Zhao,2009;Noor & Amir, 2009;Omar, 2015;Taheri & Davoudi, 2016;Baskin et al, 2017;Altalhab, 2019). Hence, explicit training on the usage of vocabulary acquisition procedures makes it easier for students to acquire new words.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the most utilized strategies by the students were the 'determination strategies and the least ones were the cognitive strategies. Altalhab (2019) explored how Saudi university students' vocabulary knowledge (N= 120) affected their proficiency to communicate in English. The average vocabulary size of Saudi EFL students at the tertiary level was found around 3000 words.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, insufficient vocabulary was the main obstacle students faced in reading comprehension. This is confirmed by Altalhab (2019) and Al fatle (2017) who argue that lack of vocabulary might lead students to difficulty in understanding reading passages because vocabulary plays an important role in order to comprehend reading texts. Vocabulary is the most important part in language learning and language use (Gu, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 71%
“…In the same vein, Abedi (2017) found that lack of familiarity with vocabulary knowledge in test passages was an important element affecting EFL learners on a reading comprehension test. Al-Khasawneh (2019) and Altalhab (2019) found that the strength of the relationship between word knowledge and reading ability of EFL students increased as their grade level progressed.…”
Section: Alls 12(2):59-69mentioning
confidence: 99%
See 1 more Smart Citation